(untitled) (Third Sector Social Economic Review, 2020)
The taxation process that occurs with the tax-generating event ends with the tax collected by the state. As a result of this process, while there is an increase in public revenues, the income of taxpayers decreases. While taxpayers with tax consciousness perceive this reduction in their income as a citizenship duty, taxpayers who are not tax consciousness are in pursuit of ways to reduce the amount of tax they would pay. The concept of tax consciousness, which is an important factor in terms of tax revenues, has been tried to be measured by the survey method in the literature. The conducted surveys covering a certain region or segment is not sufficient to measure tax consciousness. In this study, a formula proposal is developed to measure the annual tax awareness in Turkey over the years 2006-2018 as calculated by the United Nations Development Program in reference to the “Human Development Index”. The findings are referred to as the “Tax Consciousness Index (TCI)”. The TCI consists of a value between 0 and 1, and the value converging to 1 indicates that tax consciousness has increased, and the value converging to 0 means that tax consciousness has decreased. Consequently, upon examining the index values over the specified years, it is seen that the index value reached the highest value (0.65) in 2007, and the lowest value (0.29) in 2014. It is thought that the effects of tax regulations such as tax amnesties, conciliation, and the state’s tax control structure are intense in determining the index values. It is thought that this study would serve as guidance in determining the variables used in determining the TCI value by developing or changing the regular dataset.